Think outside the box (2)

Calculus Level 3

Let f ( 0 ) ( x ) = ( 9 x 2 x 3 100 ) 99 f^{(0)}(x) = (9x^2-x^3-100)^{99} , where f ( n ) ( x ) f^{(n)}(x) denotes the n th n^\text{th} derivative of f ( x ) f(x) . If the value of f ( 3 ) ( 0 ) f^{(3)}(0) is in the form k × 10 0 98 -k\times 100^{98} , where k k is a natural number. Find the value of k k .


Check out the easier problem .


The answer is 594.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Coefficient of x n x^n in f ( x ) f(x) is 1 n ! f ( n ) ( 0 ) \displaystyle \frac{1}{n!}f^{(n)}(0) .

so using simple methods we determine coefficient of x 3 x^3 is 99 × 10 0 98 -99\times 100^{98} .

1 3 ! f ( 3 ) ( 0 ) = 99 × 10 0 98 f ( 3 ) ( 0 ) = 594 × 10 0 98 \displaystyle \frac{1}{3!}f^{(3)}(0)=-99\times 100^{98}\implies f^{(3)}(0)=\boxed{-594}\times 100^{98}

Simple methods ?

Sabhrant Sachan - 4 years, 7 months ago

Log in to reply

By simple I mean standard methods of multinomial coeffcients

Aditya Narayan Sharma - 4 years, 7 months ago

Log in to reply

Very good 😃, it will be better if you can show the full solution. Try to solve my new question.

Sabhrant Sachan - 4 years, 7 months ago

yeah!did the same way

Rohith M.Athreya - 4 years, 7 months ago

Let y ( x ) = 9 x 2 x 3 100 y(x) = 9x^2 - x^3 - 100 , then we have:

\(\begin{array} {} y (x) = 9x^2 - x^3 - 100 & \implies y(0) = - 100 \\ y' (x) = 18x - 3x^2 & \implies y'(0) = 0 \\ y'' (x) = 18 - 6x & \implies y''(0) = 0 \\ y''' (x) = - 6x & \implies y'''(0) = -6 \\ y^{(n)} (x) = 0 \text{ for } n \ge 4 \end{array} \)

f ( 0 ) ( x ) = y 99 f ( 1 ) ( x ) = 99 y 98 y f ( 2 ) ( x ) = 99 98 y 97 ( y ) 2 + 99 y 98 y f ( 3 ) ( x ) = 99 98 97 y 96 ( y ) 3 + 99 98 y 97 2 y y + 99 98 y 97 y y + 99 y 98 y f ( 3 ) ( 0 ) = 0 + 0 + 0 + 99 ( 100 ) 98 ( 6 ) = 594 10 0 98 \begin{aligned} f^{(0)}(x) & = y^{99} \\ f^{(1)}(x) & = 99y^{98}y' \\ f^{(2)}(x) & = 99 \cdot 98 y^{97}(y')^2 + 99y^{98}y'' \\ f^{(3)}(x) & = 99 \cdot 98 \cdot 97 y^{96}(y')^3 + 99 \cdot 98 y^{97}\cdot 2y'y'' + 99 \cdot 98 y^{97}y'y'' + 99y^{98}y''' \\ f^{(3)}(0) & = 0 + 0 + 0 + 99(-100)^{98}(-6) \\ & = -594 \cdot 100^{98} \end{aligned}

k = 594 \implies k = \boxed{594}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...